Pieśń ku niebiosom. Echa chopinowskie w twórczości Artura Oppmana - Sikorska-Krystek, Aleksandra; Krystek, Jędrzej (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
This article presents a cycle of lyrical works entitled Z motywów Chopina (From Chopin’s themes) by Artur Oppman, published in 1893 in the volume Pieśni (Songs). The shape of this cycle had been modified over the years. In 1908, the poet changed its title and expanded it with new works. This change testifies to the evolution of the creative concept and the set of ideas about the function of the composer’s work. Contrary to the opinion rooted in the tradition of research about the conventional approach to the impact of Chopin’s work presented in Oppman’s lyrical poetry, the authors of the article demonstrate a far-reaching originality of the discussed work, focusing their attention both on issues related to understanding the narrowly-defined poetological knowledge and on the problem of translating musical means of expression into the language of a literary work.